THE EMPLACEMENT OF THE VERMION NAPPE IN THE AREA OF KATO SELI (MT VERMION, CENTRAL MACEDONIA, GREECE) - Georgiadis, G.A.; Tranos, M.D.; Kilias, A.A.; Mountrakis, D.M. (Bulletin of the Geological Society of Greece, 2016)
Our fieldwork in the area of Kato Seli of Mt Vermion suggests that the Vermion Nappe is not only tectonically overlying the Maastrichtian flysch of the Pelagonian Zone, but also a Jurassic melange that overlies the Triassic-Jurassic marbles of the Pelagonian Zone. Moreover, between the Vermion Nappe and the underlying melange, tectonic slivers of meta-sandstones-meta-rudites are tectonically emplaced. This calls for a reassessment of the emplacement of the Vermion Nappe and its role in the geotectonic evolution of the area.